Análise comparativa por meio de tratamento por imagem dos contatos oclusais em boca e em aparelhos mecânicos - Guilherme Campos Vieira (2007)
The purpose of this study was to verify the qualitative discrepancy present on the oclusal surface contact points of teeth 27, 26, 25 and 24 on different patients when comparing with "in vivo" digital images, as well as those of models set up in verticulator, in the semi-adjustable articulator "non arcon" (Gnatus - JP30®) and in an "arcon" device (Whip-Mix®). Two patients were selected for this experiment, resulting in six total models which were, mounted on two semi-adjustable devices and on six partial ones, by means of the molding of a double arch, being sequentially mounted on a verticulator. A device for obtaining intra-oral photographs bearing the same focal distance and plane was developed and manufactured. For the register of the oclusal contacts a carbon paper 0,8 mm of thickness and a specific intra-oral camera was used. The photographs thus obtained were duly organized for later comparison and qualitative evaluation. As well as on the methodology used, based on the results, it was conclude that the used mechanical devices well reproduced the oclusal contacts in the mouth, despite their limitations. The methodology of digitalized images can make qualitative comparisons of those contacts obtained in mouth and mechanical devices. The methodology of created images digitalization allowed the qualitative comparison of the contacts in mouth but is necessary greater development to allow a quantitative analysis.